Topical Almond Oil for Prevention of Pressure Injuries: A Single-Blinded Comparison Study. Issue 4 (July 2020) - Borzou, Seyed Reza; Amiri, Sheller; Azizi, Azim; Tapak, Leili; Rahimi Bashar, Farshid; Moradkhani, Shirin
Abstract : PURPOSE: The aim of our study was to determine the effect of topical almond oil for prevention of pressure injuries. DESIGN: Single-blind randomized clinical trial. SAMPLE AND SETTING: Patients admitted to an intensive care unit in Besat Hospital, Hamadan, Iran, were invited to participate in the trial. Data were collected over an 8-month period. METHODS: A convenience sample of 108 patients, using a permuted block randomization method was assigned to 3 equal groups that received the intervention almond oil, placebo (liquid paraffin), or control (standard of care). Data included demographic information, Braden Scale score, and National Pressure Ulcer Advisory Panel—European Pressure Ulcer Advisory Panel (NPUAP—EPUAP) pressure injury staging system classification score. The intervention and placebo groups received daily application of 6.5 cc of topical almond oil or paraffin to the sacrum, heels, and shoulders for 7 consecutive days. The skin was evaluated for pressure injuries by an expert nurse who was blinded to groups. Chi-square test, analysis of variance, and regression analyses were used to evaluate relationships within and between groups for study variables, incidence of pressure injuries, and duration of time of onset of pressure injuries. P values less than .05 were deemed statistically significant. RESULTS: The incidence of pressure injury in the almond oil group (n = 2; 5.6%) was lower than that in the placebo (n = 5; 13.9%, P = .189) or control groups (n = 9; 25.1%, P = .024). The incidence of pressure injuries in the control group was 6.8 and 2.12 ( P = .227) times higher than that in the almond and placebo groups, respectively. The onset day of a pressure injury occurred 5.4 days after initiation of the protocol in the almond oil group compared to 4.22 days in the control group ( P = .023) and 5 days in the placebo group ( P = .196). CONCLUSION: The topical application of almond oil was associated with a lower incidence of pressure injuries and that developed later during the study compared to participants who received paraffin or standard of care only. Further study is recommended to advance this work in populations at risk for pressure injury.